Spinal Subdural Abscess following Transforaminal Lumbar Interbody Fusion - Isamu Miura; Motoo Kubota; Oji Momosaki; Kento Takebayashi; Takakazu Kawamata; Masahito Yuzurihara (Case Reports in Orthopedics)
Spinal subdural abscesses are rare lesions. We report the case of surgical site infection complicated with meningitis and rapidly progressive spinal subdural abscess caused by P. aeruginosa following transforaminal lumbar interbody fusion (TLIF). A 72-year-old woman was admitted to our hospital complaining of drop foot syndrome and sciatica caused by stenosis of the L5/6 intervertebral foramen accompanied by L5 lumbar vertebral fracture. Accordingly, TLIF of L5-L6 and balloon kyphoplasty of L5 were performed. On the 3rd postoperative day (POD), she was diagnosed with surgical site infection complicated with bacterial meningitis. Subcutaneous fluid, blood, and cerebrospinal fluid cultures indicated P. aeruginosa. On the 7th POD, a repeat MRI showed a large dorsal fluid collection consistent with a subdural infection and massive cauda equina compression. We performed debridement and instrument removal and found a dural laceration that was not observed during the first operation. An intraoperative insensible dural laceration may cause bacteria intrusion into the subdural space.